Profil Keterampilan Berpikir Kritis Mahasiswa pada Materi Fisiologi Tumbuhan - Any Fatmawati; I Wayan Karmana (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Critical thinking skills are skills needed by students in learning science. The purpose of this study was to determine the profile of students' critical thinking skills in plant physiology material. This type of research is a survey. Participants were 99 students (45 male and 54 female) from the Department of Biology Educationin Mataram, NTB. The research was conducted from July 2019 to March 2020. The instrument for critical thinking skills was in the form of an essay test on plant physiology as many as 11 questions which were declared valid and reliable. Critical thinking skills instrument based on FRISCO indicators (Focus, Reason, Inference, Situation, Clarity, and Overview). Data analysis was carried out descriptively. The results showed: 1) male and female students have differences in critical thinking skills; and 2) there is a significant difference between students' critical thinking skills based on gender, the average critical thinking skills of men are 50.65 and women are 54.62 with the category not yet well developed. The results showed that it is necessary to empower students' critical thinking skills.